Pengembangan Sistem Informasi Pengelolaan Inventaris dengan Metode Agile Feature Driven Development - Wahyudi, Eka; Kharisma, Kharisma; Tasya Aldawiyah , Syarifah; Reghita , Lola (Applied Information Technology and Computer Science (AICOMS), 2022)
Inventory of facilities and equipment in higher education is an important means inlearning, research and community service activities, especially in vocational education which implements a learning model by applying the concept of 60% practical learning and 40% theoretical learning. tools and facilities in higher education need to be managed properly so that lecture activities can be carried out and run well. The implementation of an information system for inventory management aims to simplify the process of collecting data on facilities and tools at Politap. One of the obstacles in the data collection process so far is the large number of facilities and equipment scattered in each department and the ineffective and inefficient method of reporting the condition of facilities and equipment. The development of a web-based inventory management information system aims to solve these problems by simplifying the inventory management process. Features of the inventory information system include data collection of types, conditions, employees responsible for inventory, and departments that use inventory. The system development method used in this research uses the FDD method, system design using UML, PHP programming language with SQL database. The final result of this research is a web-based inventory management information system that facilitates service and inventory management at Politap.